I2 Huntington's disease reduced penetrance alleles occur at high frequency and affect age-related increases in prevalence. (13th September 2016) - Kay, Chris; Collins, Jennifer; Miedzybrodzka, Zosia; Wright, Galen; Madore, Steven; Gordon, Erynn; Gerry, Norman; Fisher, Emily; Davidson, Mark; Slama, Ramy; Hayden, Michael
Abstract : Background: Huntington's disease (HD) is diagnosed in 1 in 7300 individuals in Western populations but the frequency and penetrance of the causative CAG repeat expansion is unknown. Effects of population ageing, which may increase the rate of late-onset HD, remain unclear. Aims: To directly estimate the frequency and penetrance of CAG repeat alleles associated with HD, and model changes in prevalence resulting from increased ascertainment of late-onset cases. Methods: CAG repeat length was evaluated in 7315 individuals from three population-based cohorts in British Columbia, the United States, and Scotland. The frequency of CAG 36–38 repeat genotypes was compared to the prevalence of HD patients with genetically confirmed CAG 36–38 in a multisource clinical ascertainment in British Columbia, Canada. Penetrance of 36–38 CAG repeat alleles for HD was directly estimated for individuals ≥65 years of age. Age-specific prevalence rates were used to model change in prevalence as a function of population ageing and increased ascertainment of patients ≥65 years of age. Results: 18 of 7315 individuals had ≥36 CAG, revealing that approximately 1 in 400 individuals in the general population have an expanded CAG repeat associated with HD (0.246%). Individuals with CAG 36–37 genotypes are the most common (36, 0.096%; 37, 0.082%; 38, 0.027%; 39, 0.000%; ≥40, 0.041%). The prevalence of HD is expected to increase as a result of both population ageing and increased ascertainment of late-onset cases. Conclusions: The relatively infrequent diagnosis of HD at 36–38 CAG repeats suggests low penetrance in this range. Another contributing factor may be reduced ascertainment of HD in those of older age. Our data imply that population ageing will lead to higher prevalence rates of HD. Improved ascertainment of late-onset HD, particularly in the reduced penetrance range, may lead to further increases.